The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0102-311x2006000900019
|View full text |Cite
|
Sign up to set email alerts
|

Saúde da família no Estado de Mato Grosso, Brasil: perfis e julgamentos dos médicos e enfermeiros

Abstract: This article addresses the profile and assessment of the Family Health Program by physicians and nurses regarding the following aspects: profile characteristics; degree of agreement with the program's proposals; and application of methods for planning and implementing primary care activities. This was an evaluative study with health professionals, and the conclusions highlighted the following: (1) the professional profile reinforcing feminization of the healthcare work force; prevalence of precarious work cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
16

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 14 publications
0
8
0
16
Order By: Relevance
“…Among other factors, the weaknesses of primary healthcare units in terms of case resolution have been indicated as one of the problems for maintaining the strategy of changes to the care model, 5 especially regarding the hierarchical fl ow for attendance. The lack of mechanisms for regulating the municipalities' responsibilities may explain the defi ciency in the quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…Among other factors, the weaknesses of primary healthcare units in terms of case resolution have been indicated as one of the problems for maintaining the strategy of changes to the care model, 5 especially regarding the hierarchical fl ow for attendance. The lack of mechanisms for regulating the municipalities' responsibilities may explain the defi ciency in the quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…6,[8][9][10][11] Nesse sentido, esse estudo traz contribuições importantes para o conhecimento da composição e das condições de trabalho das equipes de CAPS diante da premissa de que os profissionais de saúde são atores principais para a efetiva reforma psiquiátrica no âmbito do Sistema Único de Saúde (SUS). 6,8 Houve predomínio de trabalhadores do sexo feminino com idade média de 37 anos na composição das equipes de CAPS o que é semelhante aos resultados encontrados em outros estudos com trabalhadores de saúde mental 7,12,14 e da atenção básica [15][16][17] , confirmando a feminilização da força de trabalho em saúde no Brasil.…”
Section: Discussionunclassified
“…Tal resultado é consistente cm a literatura e indica a necessidade de desprecarização do trabalho no sistema de saúde. 9,[14][15][16][18][19][20] Em relação ao tempo de atuação em serviços de saúde mental em especial a vinculação com o mesmo serviço, observou que apenas 30% dos trabalhadores estavam vinculados ao serviço a menos de 12 meses, o que se destaca como um ponto positivo para o serviço de saúde, tendo em vista que a alta rotatividade nas equipes de saúde impede a formação de vínculo e o desenvolvimento de novas práticas. 17,21 Pode-se observar também a carência de profissionais de nível técnico e com qualificação nesta área de saúde mental.…”
Section: Discussionunclassified
“…12 In turn, the Russian studies/CE and in the State of Mato Grosso, showed smaller percentages of professionals with expertise in these areas, 33% and 32.8% respectively. 13,10 As regards the time of activity of the professional persons within the ESF, the results showed that 1/3 of them played between three to five years, a percentage similar to the training time, which indicates that these began his professional activities as soon as completed graduation. Research that has assessed the implementation of IMCI in Russas/EC, showed that the professionals operating in ESF for less than a year.…”
mentioning
confidence: 96%
“…10 The significant numbers of professionals who have sought evidence of interest in specializations ensure scientific support to get the job done in the ESF. In addition, this profile shows commitment to professional performance and can understood as a way of keeping the job, due to the instability of employment in healthcare links.…”
mentioning
confidence: 99%